Anammox cultivation in a closed sponge-bed trickling filter. (June 2015) - Sánchez Guillén, J.A.; Cuéllar Guardado, P.R.; Lopez Vazquez, C.M.; de Oliveira Cruz, L.M.; Brdjanovic, D.; van Lier, J.B.
Highlights: Anammox were cultivated in closed sponge-bed trickling filters at 20 °C and 30 °C. The reactor at 30 °C achieved an early stability in terms of nitrogen removal. Both reactors reached a nitrogen removal above 80% with an HRT of only 1 h. This technology can be used for post-treatment nitrogen removal in mainstreams. Abstract: A feasibility study was carried out to assess the cultivation of Anammox bacteria in lab-scale closed sponge-bed trickling filter (CSTF) reactors, namely: CSTF-1 at 20 °C and CSTF-2 at 30 °C. Stable conditions were reached from day 66 in CSTF-2 and from day 104 in CSTF-1. The early stability of CSTF-2 is attributable to the influence of temperature; nevertheless, by day 405, the nitrogen removal performed by CSTF-1 increased up to similar values of CSTF-2. The maximum total nitrogen removal efficiency was 82% in CSTF-1 and 84% in CSTF-2. After more than 400 days of operation, CSTF-1 and CSTF-2 were capable to attain a total nitrogen removal efficiency of 74 ± 5% and 78 ± 4% with a total nitrogen conversion rate of 1.52 and 1.60 kg-N/msponge 3  d, respectively. The proposed technology could be a suitable alternative for mainstream nitrogen removal in post-treatment units via the Anammox conversion pathway.